The relationship of fantasy football participation with NFL television ratings - John A. Fortunato (Journal of Applied Sports Management, 2011)
An estimated 30 million people participate in fantasy football leagues, yet little academic research has been conducted on this topic. While there are many factors that can contribute to the television rating of a sports event, this study asks if fantasy football participation can serve as an additional motivating factor for fans to watch National Football League (NFL) games on television. Results provide some evidence that games with more NFL players starting in a high percentage of fans’ fantasy football leagues have higher Nielsen ratings, although there are differences for the games on NBC vs. ESPN, percentage of starting fantasy players, teams’ combined winning percentage, and closeness of game.
Keywords: Fantasy Sports; NFL; Television Ratings